Like a Broken Pebble from the Pavement — Two Readings on Subalternity and the Woman Condition in Saadat Hasan Manto's “The Insult” (1948) - Clara Ballart (Universitat Autònoma de Barcelona, 2018)
Manto's writings are hardly as controversial and ground-breaking as his series of short stories about Bombay's prostitutes and the world surrounding them. My paper aims to give at least two readings of the story of Saugandhi and “the insult” she receives when being rejected by a client. Her burst of pent-up rage, helpless but terrible, can be interpreted either as a positive act of realization of her own condition or as a reaffirmation of powerlessness in the face of the dominant. Using the tools of the canonic and original concept of the subaltern, with Gramsci (1916) and Spivak (1985) delimiting its oppressed (non)identity, Saugandhi's consciousness of herself becomes the voice which the subaltern cannot utter. Manto's essays (1955) show major concern with the desperate state of sexual workers, and it is through his feminism that this paper will discard the abstract notion of subalternity and highlight how gender makes “the woman who didn't have a father's shelter, had no education, ...a broken pebble from the pavement” (Manto, 2014: 204). The short story is not, as it may seem in abstract terms, empowering; it is a wretched cry that ends in silence —there is nothing to be done.